Defending against insider threats with network security's eighth layer. Issue 3 (March 2021) - Chapman, Phil
Abstract : It would be an understatement to say 2020 was a year of change, but here we are in March 2021, a world away from March 2020. As the UK Government juggles the socio-economic impacts of Covid-19 and now Brexit, daily news briefings are announcing new guidelines and initiatives to tackle a whole host of problems old and new yet it feels like the growing cyber security threat has been pushed to the bottom of the importance list. With the changes in work practices brought about by the pandemic, security teams have found themselves going back to basics. One area that needs special attention is the so-called 'layer eight' – the user. Organisations need to look at how they can reduce deliberate or inadvertent threats from insiders as working from home becomes the new normal. Businesses must implement strict network security policies, as well as looking at the role that the entire organisation plays in network security strategies, argues Phil Chapman of Firebrand Training.